The Role of Mental Imagery in Imaginative and Ecological Teaching - Judson, Gillian (Canadian Journal of Education/Revue canadienne de l'éducation, 2014)
This article explores how mental imagery evoked from words might enhance the learning of cross-curricular content and how it may help cultivate students’ ecological understanding: that deep sense of connection to a living world and the care and concern to live differently within it. With reference to Elliott Eisner’s and Kieran Egan’s works, I offer a rationale for attending more fully to mental imagery in teaching. The article concludes with a discussion of pedagogical implications for more meaningful and engaging school experiences based on students’ and teachers’ imaginative engagement with curricular content.